Spontaneous Formation of Heterodimer Au–Fe7S8 Nanoplatelets by a Seeded Growth Approach - Javaid, S.; Li, Y.; Chen, D.; Xu, X.; Pang, Y.; Chen, W.; Wang, F.; Shao, Zongping; Saunders, M.; Veder, Jean-Pierre; Jia, Guohua; Jones, Franca (AMER CHEMICAL SOC, 2019)
Hybrid nanomaterials offer increased flexibility to achieve heterostructures with controlled functionalities and predictable linkages owing to their synergistic interactions. Here, we have developed a synthetic strategy that produced hexagonal-shaped nanoplatelets (NPLs) of gold-pyrrhotite (Au-Fe7S8) with Au embedded inside them by means of a seeded growth method. Using thiol-capped Au nanoparticles (NPs) as a seed, heterogeneous nucleation of the iron precursor was facilitated, leading to the formation of Au-Fe7S8 NPLs. The injection temperature and surface ligand of the seed (Au) were two critical factors that determined the homogeneity and final morphology of the Au-Fe7S8 NPLs. This strategy was further expanded using Ag NPs as the seed to construct heterodimers, producing Ag2S-Fe7S8 heterostructures.